Challenges in Supporting Women's Recovery from Sexual Violence in a Village Setting: Addressing Social Structures in Gampong Meurandeh Dayah, Aceh - Rijal, Syamsul; Nasir, Mohd. (PALASTREN: Jurnal Studi Gender, 2024)
This article examines the structural challenges in the formation of advocacy policies for female victims of sexual violence in Gampong Meurandeh, Langsa City, Aceh. The data collection process utilized the participatory action research method over four months. Drawing upon social structure theory, the article argues that the causes of sexual violence in rural communities are not only rooted in knowledge and culture but also in the social structures that operate within these communities. The research findings indicate that the reluctance of village authorities to engage in the formulation of sexual violence policies is impeding the successful execution of sexual violence prevention programs. The article highlights two factors that hinder the prevention of sexual violence in Gampong Meurandeh Dayah. Firstly, the lack of female representation in the village government Secondly, support for victims of sexual violence is not a primary concern in the village government's policies. The article concludes that sexual violence prevention programs implemented in patriarchal communities require not only a change in public knowledge but also interventions at the structural level.